Exploring the Phytochemical and Antioxidant potential of Musa balbisiana Peel Extract Using Biochemical Approach - Syamsul Bahri; Raudatul Jannah; Ami Rahmawati; Rizky Jasa Huldin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Several studies have discussed the benefits peels of Musa balbisiana. This study aims to determine the chemical content in Kepok banana (Musa balbisiana) peel as a natural ingredient. Sample in this study is Kepok banana peel. Sliced peel of Kepok banana were dried by keeping this sample in room temperature for days, grounded using a commercial blender, and passed through a 60 mesh sieve, macerated for 72 hours using 96% ethanol, then filtered and concentrated the sample by using a rotary evaporator. Phytochemical analysis showed that ethanol extract of Kepok banana peel contain tannins, flavanoids, steroids and saponin. Radical scavenging activities (inhibition of DPPH) of the extract showed that ethanol extract of Kepok banana peel has a very strong antioxidant activity, because from a linear regression curve we obtained equation y=1.2597x – 5.7942. By using this equation, IC50 concentration value is 44.29 ppm.